Development of a wheeled inverted pendulum mobile platform with a four-bar parallel mechanism. (16th February 2018) - Jeong, Seonghee; Hayashi, Taisei
Abstract : Abstract: A wheeled inverted pendulum (WIP) offers benefits such as a small floor occupation area, high dynamic stability, and horizontal force sensitivity. However, the body of a WIP robot inclines at the start of acceleration or deceleration, when an external force is applied, or when the position of a CoG is changed. This incline may result in degraded task performance such as object dropping during delivery or image swaying when taking video. In this paper, a WIP mobile platform adopting a four-bar parallel mechanism which provides robust load position variance and horizontal posture keeping is proposed. The basic structure of this platform connects two front and rear inverted pendulums and two upper and lower bars with free-rotational joints, so as to act as a four-bar parallel link mechanism. Based on the features of the parallel mechanism, the platform can maintain a horizontal posture of the upper bar during balancing motion under various disturbances. The motion equations of the mobile platform showed that a change of the loading condition on the upper bar did not affect the balancing characteristics, as confirmed via balancing simulations. Two possible application tasks, namely object delivery and image taking, were successfully demonstrated to show the utility of the platform in terms of its horizontal posture compensation function and its robustness in terms of load position variance.